Larval body condition regulates predator‐induced life‐history variation in a dragonfly. Issue 1 (27th November 2017) - Moore, Michael P.; Lis, Cassandra; Martin, Ryan A.
Abstract: Organisms with complex life cycles commonly exhibit adaptive plasticity in the timing of transitions between life stages. While the threat of predation is predicted to induce earlier transitions, empirical support has been equivocal. When predation risk affects both the propensity to transition to the next life stage and the ability to reach the energetic thresholds necessary to complete the transition, only those individuals in the best physiological condition may be able to accelerate development and emerge earlier. To test this hypothesis, we followed uniquely marked dragonfly larvae ( Pachydiplax longipennis ) through emergence in pools where we factorially manipulated the presence of a large heterospecific predator ( Anax junius ) and cannibalism risk via conspecific size variation. Consistent with our hypothesis, high‐condition larvae were more likely to emerge in the presence of the heterospecific predator than in its absence, and low‐condition larvae were more likely to emerge in its absence than in its presence. Moreover, high‐condition larvae emerged earlier when cannibalism risk was high than when it was low. Predation risk therefore has condition‐dependent effects on emergence. As predation risk frequently affects resource accumulation, similar mechanisms across taxa could commonly underlie the incongruence between empirical results and theoretical expectations for predator‐induced life‐history variation.